Regenerated hair cells in the neonatal cochlea are innervated and the majority co-express markers of both inner and outer hair cells - Heuermann, Mitchell L.; Matos, Sophia; Hamilton, Deborah; Cox, Brandon C. (Frontiers in Cellular Neuroscience, 2022)
After a damaging insult, hair cells can spontaneously regenerate from cochlear supporting cells within the first week of life. While the regenerated cells express several markers of immature hair cells and have stereocilia bundles, their capacity to differentiate into inner or outer hair cells, and ability to form new synaptic connections has not been well-described. In addition, while multiple supporting cell subtypes have been implicated as the source of the regenerated hair cells, it is unclear if certain subtypes have a greater propensity to form one hair cell type over another. To investigate this, we used two CreER mouse models to fate-map either the supporting cells located near the inner hair cells (inner phalangeal and border cells) or outer hair cells (Deiters’, inner pillar, and outer pillar cells) along with immunostaining for markers that specify the two hair cell types. We found that supporting cells fate-mapped by both CreER lines responded early to hair cell damage by expressing Atoh1, and are capable of producing regenerated hair cells that express terminal differentiation markers of both inner and outer hair cells. The majority of regenerated hair cells were innervated by neuronal fibers and contained synapses. Unexpectedly, we also found that the majority of the laterally positioned regenerated hair cells aberrantly expressed both the outer hair cell gene, oncomodulin, and the inner hair cell gene, vesicular glutamate transporter 3 (VGlut3). While this work demonstrates that regenerated cells can express markers of both inner and outer hair cells after damage, VGlut3 expression appears to lack the tight control present during embryogenesis, which leads to its inappropriate expression in regenerated cells.